Ocean acidification research in the Mediterranean Sea: Status, trends and next steps ... : بحوث تحمض المحيطات في البحر الأبيض المتوسط: الحالة والاتجاهات والخطوات التالية ... - Abed El Rahman Hassoun; Ashley Bantelman; Donata Melaku Canu; Steeve Comeau; Charles Galdies; Jean‐Pierre Gattuso; Michele Giani; Michaël Grelaud; Iris E. Hendriks; Valeria Ibello; Mohammed Khalidi Idrissi; Εvangelia Krasakopoulou; et al. (OpenAlex, 2022)
Ocean acidification (OA) is a serious consequence of climate change with complex organism-to-ecosystem effects that have been observed through field observations but are mainly derived from experimental studies. Although OA trends and the resulting biological impacts are likely exacerbated in the semi-enclosed and highly populated Mediterranean Sea, some fundamental knowledge gaps still exist. These gaps are at tributed to both the uneven capacity for OA research that exists between Mediterranean countries, as well as to the subtle and long-term biological, physical and chemical interactions that define OA impacts. In this paper, we systematically analyzed the different aspects of OA research in the Mediterranean region based on two sources: the United Nation's International Atomic Energy Agency's (IAEA) Ocean Acidification International Coordination Center (OA-ICC) database, and an extensive survey. Our analysis shows that 1) there is an uneven geographic capacity in OA research, and illustrates that both ... : يعد تحمض المحيطات (OA) نتيجة خطيرة لتغير المناخ مع تأثيرات معقدة من كائن إلى نظام بيئي تم ملاحظتها من خلال الملاحظات الميدانية ولكنها مستمدة بشكل أساسي من الدراسات التجريبية. على الرغم من أن اتجاهات الوصول المفتوح والآثار البيولوجية الناتجة عنها من المحتمل أن تتفاقم في البحر الأبيض المتوسط شبه المغلق والمكتظ بالسكان، إلا أن بعض الفجوات المعرفية الأساسية لا تزال موجودة. وتعزى هذه الفجوات إلى كل من القدرة غير المتكافئة لأبحاث الوصول المفتوح الموجودة بين بلدان البحر الأبيض المتوسط، وكذلك إلى التفاعلات البيولوجية والفيزيائية والكيميائية الدقيقة والطويلة الأجل التي تحدد آثار الوصول المفتوح. في هذه الورقة، قمنا بتحليل منهجي للجوانب المختلفة لأبحاث الزراعة العضوية في منطقة البحر الأبيض المتوسط بناءً على مصدرين: قاعدة بيانات مركز التنسيق الدولي لتحمض المحيطات التابع للوكالة الدولية للطاقة الذرية التابعة للأمم المتحدة، ومسح شامل. يظهر تحليلنا أن 1) هناك قدرة جغرافية غير متكافئة في أبحاث الزراعة العضوية، ويوضح أن كل من الأحواض الجزائرية- البروفينية والأيونية الفرعية هي حاليًا أقل مناطق البحر الأبيض المتوسط دراسة، 2) ...